KOMUNIKASI ORANG TUA-REMAJA DAN PERILAKU PREVENTIF SEKS REMAJA DI KABUPATEN BANYUMAS - Agoeng Noegroho (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This study analyzes the effect of direct and indirect factors of parent-adolescent communication and percieved threat of health reproductive to adolescent reproductive health preventive behaviors in Banyumas. The research method is mix method with quantitative research as the dominant approach and qualitative research supported in a single research design. Sample account is 149 people as a member of the adolescent group conceling in Banyumas which taken by the census. The result shows, the adolescent reproductive health preventive behavior is influenced directly and indirectly (p <0.05) by the communication between parents-adolescent with a total effect of 0.369. Advice to parents to have communication frequently with son or daughter about reproductive health, because it will increase the adolescent sex preventive behaviors.